This theory specifies the definition and proves basic properites of loops. Loops are very similar to groups, the only property that is missing is associativity of the operation.
In this section we define the notions of identity element and left and right inverse.
A loop is a quasigroup with an identity elemen.
definition
\( \text{IsAloop}(G,A) \equiv \text{IsAquasigroup}(G,A) \wedge (\exists e\in G.\ \forall x\in G.\ A\langle e,x\rangle = x \wedge A\langle x,e\rangle = x) \)
The neutral element for a binary operation \(A:G\times G \rightarrow G \) is defined as the only element \(e\) of \(G\) such that \(A\langle x,e\rangle = x\) and \(A\langle e,x\rangle = x\) for all \(x\in G\). Note that although the loop definition guarantees the existence of (some) such element(s) at this point we do not know if this element is unique. We can define this notion h ere but it will become usable only after we prove uniqueness.
definition
\( \text{ TheNeutralElement}(G,f) \equiv \) \( ( \text{The } e.\ e\in G \wedge (\forall g\in G.\ f\langle e,g\rangle = g \wedge f\langle g,e\rangle = g)) \)
We will reuse the notation defined in the quasigroup0 locale, just adding the assumption about the existence of a neutral element and notation for it.
locale loop0 = quasigroup0 +
assumes ex_ident: \( \exists e\in G.\ \forall x\in G.\ e\cdot x = x \wedge x\cdot e = x \)
defines \( 1 \equiv \text{ TheNeutralElement}(G,A) \)
In the loop context the pair \( (G,A) \) forms a loop.
lemma (in loop0) is_loop:
shows \( \text{IsAloop}(G,A) \) unfolding IsAloop_def using ex_ident, qgroupassumIf we know that a pair \( (G,A) \) forms a loop then the assumptions of the loop0 locale hold.
lemma loop_loop0_valid:
assumes \( \text{IsAloop}(G,A) \)
shows \( loop0(G,A) \) using assms unfolding IsAloop_def, loop0_axioms_def, quasigroup0_def, loop0_defThe neutral element is unique in the loop.
lemma (in loop0) neut_uniq_loop:
shows \( \exists !e.\ e\in G \wedge (\forall x\in G.\ e\cdot x = x \wedge x\cdot e = x) \)proofThe neutral element as defined in the loop0 locale is indeed neutral.
lemma (in loop0) neut_props_loop:
shows \( 1 \in G \) and \( \forall x\in G.\ 1 \cdot x =x \wedge x\cdot 1 = x \)proofEvery element of a loop has unique left and right inverse (which need not be the same). Here we define the left inverse as a function on \(G\).
definition
\( \text{LeftInv}(G,A) \equiv \{\langle x,\bigcup \{y\in G.\ A\langle y,x\rangle = \text{ TheNeutralElement}(G,A)\}\rangle .\ x\in G\} \)
Definition of the right inverse as a function on \(G\):
definition
\( \text{RightInv}(G,A) \equiv \{\langle x,\bigcup \{y\in G.\ A\langle x,y\rangle = \text{ TheNeutralElement}(G,A)\}\rangle .\ x\in G\} \)
In a loop \(G\) right and left inverses are functions on \(G\).
lemma (in loop0) lr_inv_fun:
shows \( \text{LeftInv}(G,A):G\rightarrow G \), \( \text{RightInv}(G,A):G\rightarrow G \) unfolding LeftInv_def, RightInv_def using neut_props_loop, lrdiv_props(1,4), ZF1_1_L9, ZF_fun_from_totalRight and left inverses have desired properties.
lemma (in loop0) lr_inv_props:
assumes \( x\in G \)
shows \( \text{LeftInv}(G,A)(x) \in G \), \( ( \text{LeftInv}(G,A)(x))\cdot x = 1 \), \( \text{RightInv}(G,A)(x) \in G \), \( x\cdot ( \text{RightInv}(G,A)(x)) = 1 \)proofassumes \( x\in G \), \( y\in G \)
shows \( \exists !z.\ z\in G \wedge z\cdot x = y \), \( y/ x \in G \), \( (y/ x)\cdot x = y \) and \( \exists !z.\ z\in G \wedge x\cdot z = y \), \( x\backslash y \in G \), \( x\cdot (x\backslash y) = y \)assumes \( \exists ! x.\ x\in A \wedge \phi (x) \)
shows \( \exists a.\ \{x\in A.\ \phi (x)\} = \{a\} \), \( \bigcup \{x\in A.\ \phi (x)\} \in A \), \( \phi (\bigcup \{x\in A.\ \phi (x)\}) \)assumes \( \forall x\in X.\ b(x) \in Y \)
shows \( \{\langle x,b(x)\rangle .\ x\in X\} : X\rightarrow Y \)assumes \( x\in G \), \( y\in G \)
shows \( \exists !z.\ z\in G \wedge z\cdot x = y \), \( y/ x \in G \), \( (y/ x)\cdot x = y \) and \( \exists !z.\ z\in G \wedge x\cdot z = y \), \( x\backslash y \in G \), \( x\cdot (x\backslash y) = y \)assumes \( f:X\rightarrow Y \), \( x\in X \) and \( f = \{\langle x,b(x)\rangle .\ x\in X\} \)
shows \( f(x) = b(x) \) and \( b(x)\in Y \)assumes \( x\in G \), \( y\in G \)
shows \( \exists !z.\ z\in G \wedge z\cdot x = y \), \( y/ x \in G \), \( (y/ x)\cdot x = y \) and \( \exists !z.\ z\in G \wedge x\cdot z = y \), \( x\backslash y \in G \), \( x\cdot (x\backslash y) = y \)